Comparison of sequential CT arterioportography-arteriosplenography with standard cross-sectional imaging and endoscopy in children with portal hypertension - Simone Hammer; Florian Zeman; Hans Jürgen Schlitt; Christian Stroszczynski; Barbara Greiner; Michael Christian Doppler; Wibke Uller (Scientific Reports, 2022)
Abstract In this study the diagnostic capability and additional value of sequential CT arterioportography–arteriosplenography (CT AP–AS) in comparison to standard cross-sectional imaging and upper gastrointestinal endoscopy (UGE) in pediatric portal hypertension (PH) was analyzed. Patients with clinical signs of PH who underwent CT AP–AS in combination with additional contrast-enhanced magnetic resonance imaging (CE-MR) and/or contrast-enhanced computed tomography (CE-CT) were included. Two radiologists reviewed independently imaging regarding the capability to prove patency of (1) extrahepatic and intrahepatic main stem portal vein (PV), (2) intrahepatic PV system and (3) splenomesenteric venous axis. Imaging was reviewed for detection of abdominal varices and results were compared to UGE. Main venous supply of varices (PV and/or splenic vein system) and splenorenal shunting were evaluated. 47 imaging studies (20 CT AP-AS, 16 CE-MR, 11 CE-CT) and 12 UGE records of 20 patients were analyzed. CT AP–AS detected significantly more splenorenal shunts (p = 0.008) and allowed more confident characterization of the extra-/intrahepatic PV-system and splenomesenteric veins in comparison to CE-MR (p < 0.001). Extra- and intrahepatic PV-system were significantly more confidently assessed in CT AP–AS than in CE-CT (p = 0.008 and < 0.001 respectively). CT AP–AS was the only modality that detected supply of varices and additional gastric/duodenal varices. In this retrospective study CT AP–AS was superior to standard cross-sectional imaging concerning confident assessment of the venous portosplenomesenteric axis in pediatric patients. CT AP–AS detected additional varices, splenorenal shunting and supply of varices.